2009
DOI: 10.1517/17425250903124363
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacology of esomeprazole and its role in gastric acid related diseases

Abstract: Esomeprazole (S-isomer of omeprazole) demonstrates a better pharmacokinetic/pharmacodynamic profile than the racemic product omeprazole. Esomeprazole's pharmacological activity of gastric acid secretion is through proton pump inhibition. The pharmacokinetic properties provide for an enhanced pharmacological effect. Esomeprazole is rapidly absorbed and the extent of absorption is higher resulting in higher systemic absorption of esomeprazole (bioavailability), which coupled with reduced clearance results in gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 92 publications
1
10
0
3
Order By: Relevance
“…After 12 months of PPI therapy, pH‐metry demonstrated a good oesophageal pH control in both groups, with pH values lower than usual values, as measured off‐therapy. However, we observed also a higher effectiveness of esomeprazole over pantoprazole in reducing AET, consistently with the findings of previous studies 32, 33 . In particular, Miner et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…After 12 months of PPI therapy, pH‐metry demonstrated a good oesophageal pH control in both groups, with pH values lower than usual values, as measured off‐therapy. However, we observed also a higher effectiveness of esomeprazole over pantoprazole in reducing AET, consistently with the findings of previous studies 32, 33 . In particular, Miner et al.…”
Section: Discussionsupporting
confidence: 93%
“…However, we observed also a higher effectiveness of esomeprazole over pantoprazole in reducing AET, consistently with the findings of previous studies. 32,33 In particular, Miner et al 34 showed that esomeprazole (40 mg once daily), at the steady-state (day 5), achieved a higher per cent of time with intragastric pH higher than 4.0 over 24 h, when compared with standard-dose lansoprazole, omeprazole, pantoprazole or rabeprazole in patients with symptoms of GERD. Moreover, dose escalation with oral esomeprazole and pantoprazole (patients treated once-daily with either drug at 20, 40 and 80 mg, for 5 days) improved the acid control in patients with GERD, although esomeprazole allowed a significantly better control on a milligram-per-milligram basis.…”
Section: Discussionmentioning
confidence: 99%
“…2 This explains better and longer acid suppression and has been suggested to be the basis for improved clinical efficacy. 3 Regardless of the advantage in bioavailability, comparative studies between omeprazole and esomeprazole have displayed conflicting data with some meta-analyses presented a small while significant advantage in esophagitis healing, while other studies indicated no significant difference in effectiveness. 4,5 This clearly would have a big influence on cost difference where healthcare delivery system in every country is pressed to adopt innovative and new health technologies in an evidence-based manner, while making sure that they can be managed within obtainable resources.…”
Section: Disease (Gerd) Andmentioning
confidence: 99%
“…Proton pump inhibitors (PPI) reduce gastric acid secretion through inhibition of the H + /K +-ATPase in the gastric parietal cells (2)(3)(4)(5)(6), and PPI's are widely used in clinical practice to treat acid-related diseases (7). It has been reported that PPI can also protect the gastric mucosa (8)(9).…”
Section: Introductionmentioning
confidence: 99%